DexA70, the Truncated Form of a Self-Produced Dextranase, Effectively Disrupts Streptococcus mutans Biofilm - Liu, Nan; Li, Xin; Wang, Maofeng; Zhang, Fengyu; Wang, Chuandong; Zhang, Kundi; Wang, Hongwei; Xu, Sujuan; Hu, Wei; Gu, Lichuan (Frontiers in Microbiology, 2021)
Billions of people suffer dental caries every year in spite of the effort to reduce the prevalence over the past few decades. Streptococcus mutans is the leading member of a specific group of cariogenic bacteria that cause dental caries. S. mutans forms biofilm which is highly resistant to harsh environment, host immunity and antimicrobial treatments. In this study, we found that S. mutans biofilm is highly resistant to both antimicrobial agents and lysozyme. DexA70, the truncated form of DexA (amino acids 100-732), a dextranase in S. mutans, prevents S. mutans biofilm formation and disassembles existing biofilms within minutes at nanomolar concentrations when supplied exogenously. DexA70 treatment markedly enhances biofilm sensitivity to antimicrobial agents and lysozyme, indicating its great potential in combating biofilm-related dental caries.